2022
DOI: 10.1007/s42452-022-04945-w
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic water purification under visible light using carbon nitride materials and β-Bi2O3 immobilized on electrospun polyvinyl acetate fibers

Abstract: We report on the immobilization of carbon nitride (CN) materials and β-Bi2O3 on electrospun polyvinyl acetate (PVAc) fiber substrates using a dispersion based dip coating process. The spinning process was optimized by variation of several parameters to finally obtain continuous droplet-free fibers at 15 kV and a flow rate of 50 µL min−1 using a needle with 1.2 mm diameter. The polymer substrates were coated with the β-Bi2O3 and CN materials, which were characterized using SEM and applied in the photocatalytic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Recently, Bi 2 O 3 was used as a highly efficient photocatalyst to decompose RhB in the presence of different light sources due to the different reactive oxygen species (ROSs) generated by Bi 2 O 3 in the presence of light [59,60]. Generally, Bi 2 O 3 can degrade RhB pollutants through the production of reactive substances (•O −2 , •OH, h + , and e − ) [61,62]. Liu et al [63] reported that Bi 2 O 3 nanoparticles exhibited good activity against RhB pollutants due to the microstructure of the Bi 2 O 3 nanoparticles and the oxygen vacancy defects of the fluorite structure.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Bi 2 O 3 was used as a highly efficient photocatalyst to decompose RhB in the presence of different light sources due to the different reactive oxygen species (ROSs) generated by Bi 2 O 3 in the presence of light [59,60]. Generally, Bi 2 O 3 can degrade RhB pollutants through the production of reactive substances (•O −2 , •OH, h + , and e − ) [61,62]. Liu et al [63] reported that Bi 2 O 3 nanoparticles exhibited good activity against RhB pollutants due to the microstructure of the Bi 2 O 3 nanoparticles and the oxygen vacancy defects of the fluorite structure.…”
Section: Introductionmentioning
confidence: 99%